2015
DOI: 10.1021/acs.biochem.5b00483
|View full text |Cite
|
Sign up to set email alerts
|

Sbi00515, a Protein of Unknown Function from Streptomyces bingchenggensis, Highlights the Functional Versatility of the Acetoacetate Decarboxylase Scaffold

Abstract: The acetoacetate decarboxylase-like superfamily (ADCSF) is a group of ~4000 enzymes that, until recently, was thought to be homogeneous in terms of the reaction catalyzed. Bioinformatic analysis shows that the ADCSF consists of up to seven families that differ primarily in their active site architectures. The soil-dwelling bacterium Streptomyces bingchenggensis BCW-1 produces an ADCSF enzyme of unknown function that shares a low level of sequence identity (~20%) with known acetoacetate decarboxylases (ADCs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
(52 reference statements)
2
7
0
Order By: Relevance
“…As shown in Fig. 2(a), the overall fold of the Swit_4259 protomer is nearly identical to that of the proto-typical family I ADCs, as well as the recently described family V enzymes such as SbAD from Streptomyces bingchenggensis and MppR from S. hygroscopicus (not shown), which are not decarboxylases (Burroughs et al, 2013;Mueller et al, 2015). This fold, dubbed the -cone (Ho et al, 2009) or double-barrel fold (Tagaki & Westheimer, 1968), consists of a large, antiparallel, 13-stranded -sheet that forms the main barrel and folds back on itself to form a second, orthogonal barrel (Fig.…”
Section: Overall Structure Of Swit_4259supporting
confidence: 64%
See 4 more Smart Citations
“…As shown in Fig. 2(a), the overall fold of the Swit_4259 protomer is nearly identical to that of the proto-typical family I ADCs, as well as the recently described family V enzymes such as SbAD from Streptomyces bingchenggensis and MppR from S. hygroscopicus (not shown), which are not decarboxylases (Burroughs et al, 2013;Mueller et al, 2015). This fold, dubbed the -cone (Ho et al, 2009) or double-barrel fold (Tagaki & Westheimer, 1968), consists of a large, antiparallel, 13-stranded -sheet that forms the main barrel and folds back on itself to form a second, orthogonal barrel (Fig.…”
Section: Overall Structure Of Swit_4259supporting
confidence: 64%
“…The high degree of structural similarity between the MppR, SbAD and Swit_4259 active sites suggested that the latter enzyme would also accept an -keto acid as a substrate. Our previous work on SbAD found that Tyr252 plays a key role in the aldolasedehydratase activity of this enzyme (Mueller et al, 2015). Likewise, the equivalent residue in MppR, Glu283, appears to be important for its cyclization reaction (Burroughs et al, 2013).…”
Section: Functional Characterizationmentioning
confidence: 89%
See 3 more Smart Citations